Preserving Temple Murals in Isan: Wat Chaisi, Sawatthi Village, Khon Kaen, as a Sustainable Model - Brereton, Bonnie Pacala (The Journal of the Siam Society, 2015)
Wat Chaisi in Sawatthi village, Sawatthi District, located about twenty kilometers from the bustling provincial capital of Khon Kaen, is a unique example of local cultural heritage preservation that was accomplished solely through local stakeholders. Its buildings, as well as the 100 year-old murals on the ordination hall, have been maintained and are used regularly for merit-making and teaching. The effort was initiated by the abbot and is maintained through the joint effort of the wat community, Khon Kaen Municipality, and various individuals and faculties at Khon Kaen University. This paper will examine the role of local leadership in promoting local cultural heritage.